Terrestrial travel in muriquis (Brachyteles arachnoides) a cross a forest clearing at the Estação Biológica de Caratinga, Minas Gerais, Brazil - Dib, Laiena R. T.; Oliva, Andréia S.; Strier, Karen B. (Neotropical Primates, 1997)
No abstract